Communicational confrontations: Longitudinal analysis of a media-based contest - SanMartín, Ana N. (2024)
The media-based communication between social movements and other actors is relevant to achieve their goals. This article addresses the dynamic and contentious aspects of the media-based communication generated by the Magallanes Social Movement and the Government of Chile. A quantitative analysis was made of 217 news and 499 quotations published during the events. The results indicate that the parties adopted differing communication strategies like making calls for action, talking positively about the own group, among others. Furthermore, the content of communications varied over time, but the strong relation between the communications issued and the occurrence of particular protest events suggests that while a communicational contest is certainly an interactive process, both camps do not just argue through the words, but also through the events that each camp organizes.